2016
DOI: 10.1165/rcmb.2015-0095oc
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Interstitial Lung Fibroblasts Is Regulated by Platelet-Derived Growth Factor Receptor α Kinase Activity

Abstract: Epithelial-mesenchymal cell interactions and factors that control normal lung development are key players in lung injury, repair, and fibrosis. A number of studies have investigated the roles and sources of epithelial progenitors during lung regeneration; such information, however, is limited in lung fibroblasts. Thus, understanding the origin, phenotype, and roles of fibroblast progenitors in lung development, repair, and regeneration helps address these limitations. Using a combination of platelet-derived gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 93 publications
(125 citation statements)
references
References 49 publications
6
119
0
Order By: Relevance
“…In contrast, expression of CD29 (β1 integrin) identified proliferative myofibroblasts. Our previously published realveolarization data suggested that PDGFRα + /CD29 + /CD34 + fibroblasts contribute to the transient re-emergence of αSMA + myofibroblasts as they lose CD34 expression (Green et al, 2016). We performed flow cytometry to determine whether similar functional differences within PDGFRα + (CD140a + ) fibroblasts are associated with CD29 and CD34 during lung development.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, expression of CD29 (β1 integrin) identified proliferative myofibroblasts. Our previously published realveolarization data suggested that PDGFRα + /CD29 + /CD34 + fibroblasts contribute to the transient re-emergence of αSMA + myofibroblasts as they lose CD34 expression (Green et al, 2016). We performed flow cytometry to determine whether similar functional differences within PDGFRα + (CD140a + ) fibroblasts are associated with CD29 and CD34 during lung development.…”
Section: Resultsmentioning
confidence: 99%
“…PDGFRα + lung fibroblasts are essential for alveolarization and realveolarization (Green et al, 2016; Bostrom et al, 2002, 1996; Lindahl et al, 1997; Chen et al, 2012; Perl and Gale, 2009). As early as E12.5, a population of PDGFRα-expressing, SHH-responsive Gli1+ mesenchymal cells can be traced throughout postnatal lung development and contribute to nearly all of the alveolar myofibroblasts required for septation (Li et al, 2015; Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations